Snowfall surprise - Mason, Jane B.; Hines-Stephens, Sarah (New York : Scholastic Inc., 2009)
"Savannah Heglund is going to have the best birthday ever--she's spending a whole week at her family's mountain cabin with her two best friends, snowboarding and sledding and ice-skating the days away. But then all her plans go downhill, fast: On the very first day, Savvy takes a spill on her snowboard. Her perfect birthday is ruined...and worse, her friends seem to be having more fun without her. Savvy feels snowed in, but maybe the biggest surprise is yet to come!"--P. [4] of cover.
"A candy apple book"--P. [1] of cover.
G6
Keywords: Birthdays -- Juvenile fiction; Best friends -- Juvenile fiction; Winter sports -- Juvenile fiction; Snowboarding -- Accidents -- Juvenile fiction; Birthdays -- Fiction; Best friends -- Fiction; Winter sports -- Fiction; Snowboarding -- Accidents -- Fiction